Simulasi Perancangan Logo Aplikasi Clubhouse - Jennife Claudy; Jessica Marcella; Shefira Marcelline; Brian Alvin Hananto (Universitas Multimedia Nusantara, 2021)
Clubhouse is an application which has gained popularity in the past year. Despite being popular, the application doesn’t have any logo to help itself differentiate itself from other applications in terms of visual branding. To respond to this issue, the author attempted to create a logo design simulation for Clubhouse using the design methodology from Robin Landa. The result is a logo simulation for Clubhouse that is responded easily to remember from 90.5% of the respondents. Though only a simulation, the author hopes that this article may serve as a reference on a logo design process. Keywords: design simulation; logo; clubhouse